Neurofibromatosis Type 1 and Sporadic Optic Gliomas - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The natural history of sporadic optic gliomas was compared with that of optic gliomas associated with neurofibromatosis type 1 (NF1) in a study using a Children's Tumor Registry (CTR) and an NF1 Database (NF1DB) at St Mary's Hospital, Manchester, UK.